Voice or Gesture in the Operating Room - Mentis, Helena; O'Hara, Kenton; Gonzalez, Gerardo; Sellen, Abigail; Corish, Robert; Criminisi, Antonio; Trivedi, Rikin; Theodore, Pierre (2015 Human Factors in Computing Systems, 2015)
This case study represents our efforts to investigate the uses of voice control versus gestural control in the OR. We present a system we expressly built to allow for both gestural or voice control at the choice of the surgeon. We explain our deployment of this system in the context of cardiothoracic surgery and present a vignette on how the system was used in the moment by the attending surgeon. We learn that, in terms of design, its not just a question of saying voice is better for one type of functionality and gesture is better for another; rather, the benefits are circumstantial. Thus, there is a case for building in redundancy in control with both voice and gesture.